(untitled) (Journal of Comparative & International Higher Education, 2024)
The Gita, a classic of Hinduism, has been studied over different periods and perspectives. In this study, the Gita was studied as a pedagogical text and analyzed founded on the theory of deconstruction vis-à-vis postmethod pedagogy. It was discovered that, as a teacher, Lord Krishna used deconstruction in his pedagogy, so he was identified as a deconstructionist teacher. Then, this role of a teacher was further discussed with reference to the role of a teacher in postmethod pedagogy and concluded that deconstructionist is the most significant role of a teacher in postmethod pedagogy. Thus, this study claims that if teachers play the role of a deconstructionist teacher in pedagogy, quality in education can be ascertained.